Identification and Antimicrobial Activity of Marine Streptomyces from Geographically Different Regions of Indonesia - Rofiq Sunaryanto; Anis Herliyani Mahsunah (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2015)
Identification and antimicrobial assay of indegenous marine Streptomyces have been conducted. Samples were obtained from culture collection of Biotech Center, Agency for the Assessment and Application of Technology (BPPT). They were originated from several Indonesian seashores including Pelabuhan Ratu, Pangandaran, Manokwari, Pulau Seribu, Garut, Bangka, Banjarmasin, Belitung, Cirebon, and Palu. Isolates stored as glycerol stocks were inoculated onto HV (Humic acid vitamin) agar and incubated for 5 days at 30 °C. Each colony was cultivated using yeast-peptone medium and then extracted by butanol. Antimicrobial activities were monitored by the agar diffusion paper-disc method against Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923, Bacillus subtilis ATCC 66923, Pseudomonas aeruginosa ATCC 27853, Candida albicans BIOMCC 00122 and Aspergillus niger BIOMCC 0013. Molecular identification of Streptomyces was carried out based on 16S rRNA gene analysis. Our research results showed that 71 isolates obtained from several Indonesian seashore were identified as 57 different Streptomyces species. Fifty of them showed antimicrobial activity. Twenty three isolates inhibited B. subtilis ATCC 66923, 14 isolates inhibited S. aureus ATCC 25923, 24 isolates inhibited C. albicans BIOMCC 00122 and 26 isolates inhibited A. niger BIOMCC 0013 and there was no active isolates inhibited the growth of E. coli ATCC 25922 and P. aeruginosa ATCC 27853. Phylogenetic analysis showed that Streptomyces isolates originated from the same geographically region was not necessarily grouped into the same cluster. Likewise a phylogenetic cluster may contain isolates of the same Streptomyces species, but from geographically different locations.